2002
DOI: 10.1046/j.1460-9568.2002.02412.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal sonic hedgehog injection increases Patched transcript levels in the adult rat subventricular zone

Abstract: The morphogen sonic hedgehog (Shh) is implicated in neural tissue patterning and the growth of brain structures during embryogenesis and postnatal development and is also present in the adult brain. Shh signals through interaction with the tumour suppressor Patched (Ptc). This receptor for Shh is associated with Smoothened (Smo), a protein with high homology to the G-protein coupled receptors. However, little is known about the transduction mechanisms implicated in Shh signalling in the adult brain. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 34 publications
(54 reference statements)
5
31
0
1
Order By: Relevance
“…phenotype of conditional Shh signaling mutants (Machold et al, 2003) and with the increase in Ptch1 expression observed after injection of Shh into the striatum (Charytoniuk et al, 2002). However, we further show that in vitro addition of Shh results in an increase in SVZ cell proliferation and in the number of cells with stem cell properties and resulting neurons, while blocking its function decreases their number.…”
Section: Introductionmentioning
confidence: 47%
“…phenotype of conditional Shh signaling mutants (Machold et al, 2003) and with the increase in Ptch1 expression observed after injection of Shh into the striatum (Charytoniuk et al, 2002). However, we further show that in vitro addition of Shh results in an increase in SVZ cell proliferation and in the number of cells with stem cell properties and resulting neurons, while blocking its function decreases their number.…”
Section: Introductionmentioning
confidence: 47%
“…2,3,7,9,12,20,24,26 The introduction of the somewhat responsive cellular phenotype into our study design increased its analytical precision and may have eliminated some of the well-known methodical limitations associated with cell culture studies.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription-PCR experiments have located Shh mRNA in the cortex and tectum of E-13.5 mice, with continued expression through P5. Shh is expressed in progenitors of the subventricular zone (Charytoniuk et al, 2002) and stimulates proliferation of precursor cells in the ventricular zones of the telencephalon and mesencephalon and normal levels of proliferation can be attenuated with Shh inhibitors (Dahmane et al, 2001). More recent experiments have directly linked Shh signaling to proliferation of adult neural stem cells in the rat hippocampus.…”
Section: Shh Is An Important Mitogen In the Cnsmentioning
confidence: 99%